Victory as a Criteria for Ending a Conflict - Banasik, Mirosław (Roczniki Nauk Społecznych, 2026)
The aim of the research was to explain selected aspects of the theory and practice of winning considered in the context of ending a conflict. A systemic approach was used to solve the research problems, along with methods of analysis and criticism of literature and case studies. It was established that in theory and practice, there are difficulties in defining victory due to the changing nature of contemporary conflicts, which rarely end in lasting success or defeat. Victory is a highly universal and generalizing concept. It should be considered in terms of ensuring lasting peace after the end of a conflict, i.e., going beyond military success. In contemporary conflicts below the threshold of war, victory can be achieved through asymmetric political, economic, informational, and environmental campaigns in the form of indirect actions, mainly using non-military means. However, this does not mean that achieving victory without eliminating the root causes of the conflict will automatically lead to its end.